Morphological ontogeny of Melanozetes meridianus(Acari, Oribatida, Ceratozetidae) - Seniczak, Stanisław; Seniczak, Anna; Mistrzak, Marcin (Zootaxa, 2024)
The morphological ontogeny of Melanozetes meridianus Sellnick, 1928 is redescribed and illustrated. The juveniles of this species are light brown with brown prodorsum, gastronotum, sclerites and legs, and the nymphs have a well-developed lamella. In all juveniles, a humeral organ and humeral macrosclerite are present, seta c1 is inserted on humeral macrosclerite, and setae c2 and c3 are inserted on unsclerotized integument. The gastronotal shield of the larva has seven pairs of setae (d-, l-series and h1), while that of the nymphs has 10 pairs (d-, l-, h-series and p1), and setae p2 and p3 are inserted on a large posteroventral macrosclerite. In all instars the legs are stocky, all femora are flattened, and femora I and II have a large ventral carina.